Electrochemical methods for hydrogen production - Scott, K. 1951- (Research studies. Energy & environment series, 2020)
The hydrogen economy is receiving increased attention due to concerns around the consequences of fossil fuel use, and hydrogen has great potential as a way to reduce reliance on traditional energy sources. Increased hydrogen supplies using cleaner methods are seen as essential for potential hydrogen based power systems for transportation and renewable energy conversion into fuel. Electrochemical Methods for Hydrogen Production provides a comprehensive picture of the various routes to use electricity to produce hydrogen using electrochemical science and technology. The book provides an overview of the fundamentals of electrochemical cells and performance characterisation, as well as a comparison of current applications. It also includes the various types of electrolysers currently used commercially and the range of new electrolysis processes, including photo-electrochemical, biological and thermal energy techniques. Edited by an expert in the field, this title will be of interest to graduate students and researchers in academia and industry working in energy, electrochemistry, physical chemistry and chemical engineering.